2018
DOI: 10.1590/1980-549720180002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados ao bruxismo do sono em adolescentes de Teresina, Piauí

Abstract: SB is a frequent condition in adolescents, and the factors associated with its prevalence were: male sex, snoring and difficulty falling asleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 25 publications
5
15
0
17
Order By: Relevance
“…Interestingly, nocturnal breathing symptoms that were under investigation in this work showed a correlation with parental-reported tooth grinding (sleep breathing difficulties, sleep apnea, and snoring). These results are consistent with literature knowledge, which suggested an association with snoring in children [ 7 ]. Guo et al included snoring among the risk factors related to the presence of bruxism [ 6 ], as also shown by another investigation that reported a relationship with respiratory disorders during sleep [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Interestingly, nocturnal breathing symptoms that were under investigation in this work showed a correlation with parental-reported tooth grinding (sleep breathing difficulties, sleep apnea, and snoring). These results are consistent with literature knowledge, which suggested an association with snoring in children [ 7 ]. Guo et al included snoring among the risk factors related to the presence of bruxism [ 6 ], as also shown by another investigation that reported a relationship with respiratory disorders during sleep [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…For instance, a correlation between parental-reported tooth grinding and bedtime problems, such as sudden movements while falling asleep ( r = 0.234), restless legs movements, muscular pain or tingling, and falling asleep sweating, has emerged. According to Santos-Suosa et al, SB in individuals with difficulty in sleeping may be a possible result of a nervous system excitation response accompanied by body movements [ 7 ]. Furthermore, Goncalves et al in a cross-sectional study reported an association between SB and problems with falling asleep, with an OR of 4.1 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no such correlation was observed in patients with a severe form of OSA (AHI ≥ 30). One of the hypotheses linking SB and OSA is that SB activity protects against OSA by protruding the mandible and restoring airway patency [20,21]. However, this mechanism may not be adequate to prevent the airway from collapsing in severe OSA.…”
Section: Discussionmentioning
confidence: 99%